Projeto e construção de um gerador a ímãs permanentes de fluxo axial para turbina eólica de pequena potência - Thales Alexandre Carvalho Maia (2011)
The continuously growing of wind industry, the research and development stays together intending to produce new technologies even more cheap and efficient. The prove of this growing is represented through the number of installed wind turbines around the world. In Brazil, the scenario plays according to politics and economics investments, and by the positive rumors regarding the tremendous national wind power potential, even compared with hydraulics. The presented work aims to contribute with that development with the project and construction of a small axial flux permanent magnet electrical wind generator for a three blade horizontal axis wind turbine. The project has an innovation proposal in any ways, which is besides a commercial and competitive product.The sizing is worked by means of analytic equations and validated withthe help of finite element calculation software. This procedures grants some advantages in the project, which may be listed as the time processing machine through the electrical parameters variations, dimensional or materials, or through an optimization process which allowed a considerable efficiency gain and costs reduction.The mechanical modeling, as well as the considerations for the structuralproject are presented in the intent to show the interdependence of these processes in the design of an electrical machine.